2017
DOI: 10.1155/2017/7213125
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Piezoelectric Actuators and Sensors Configuration for Vibration Suppression of Aircraft Framework Using Particle Swarm Algorithm

Abstract: Numbers and locations of sensors and actuators play an important role in cost and control performance for active vibration control system of piezoelectric smart structure. This may lead to a diverse control system if sensors and actuators were not configured properly. An optimal location method of piezoelectric actuators and sensors is proposed in this paper based on particle swarm algorithm (PSA). Due to the complexity of the frame structure, it can be taken as a combination of many piezoelectric intelligent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Zoric et al [12] presented optimal actuators' sizes and locations over the first 5 modes of a smart cantilever beam by implementing fuzzy to transform controllability-based multi-objective function and constraints to pseudo-goal function, and hence, applied particle swarm optimization package to achieve the desired goal. Huang et al [26] established an experimental platform of an aircraft framework to verify the proposed method of actuators and sensors distribution. The comparison between different optimization algorithms showed that the genetic algorithm is more favorable than the particle swarm algorithm for the proposed system's vibration suppression rate .…”
Section: Introductionmentioning
confidence: 99%
“…Zoric et al [12] presented optimal actuators' sizes and locations over the first 5 modes of a smart cantilever beam by implementing fuzzy to transform controllability-based multi-objective function and constraints to pseudo-goal function, and hence, applied particle swarm optimization package to achieve the desired goal. Huang et al [26] established an experimental platform of an aircraft framework to verify the proposed method of actuators and sensors distribution. The comparison between different optimization algorithms showed that the genetic algorithm is more favorable than the particle swarm algorithm for the proposed system's vibration suppression rate .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in [21] that a large number of engineering applications require a reduction in the number of sensors and actuators used for structural dynamic behavior control. This problem leads to the need to exploit these elements in a multimodal regime.…”
Section: Introductionmentioning
confidence: 99%